Therapeutic efficacy and cognitive adverse events of overactive bladder medication in patients with central nervous system Disorders—A cohort study - Sheng-Fu Chen; Yao-Chi Chuang; Chung-Cheng Wang; Chun-Hou Liao; Hann-Chorng Kuo (Journal of the Formosan Medical Association, 2022)
Purpose: This cohort study evaluates therapeutic efficacy and adverse events (AEs) of various overactive bladder (OAB) medications for patients with central nervous system (CNS) disorders. Methods: Patients with OAB and CNS disorders were prospectively enrolled. They were randomly allocated to 3 different treatment subgroups: (1) mirabegron 50 mg once daily (2) solifenacin 5 mg per day, and (3) combined solifenacin 5 mg and mirabegron 50 mg once daily. Efficacy and safety questionnaires and objective parameters were compared among the subgroups, and subgroups between baseline and 3 and 6 months after treatment. AEs, including cognitive dysfunction, were assessed using the Mini-Mental State Examination (MMSE). Results: 102 patients (mean age, 71.8 ± 8.7 years) were enrolled, including 35, 36, and 31 patients received mirabegron monotherapy, solifenacin monotherapy, and combination therapy, respectively. OAB symptoms scores all significantly improved 3 months after treatment in different subgroup. However, PVR increased and VE decreased significantly after treatment in patients receiving solifenacin monotherapy and combination therapy. Dry mouth and constipation were the most common AEs, especially in the solifenacin and combination subgroups. Mild incidence of AEs was noted in patients receiving mirabegron monotherapy. No significant change in MMSE was noted among the subgroups after treatment. Conclusion: OAB medication had good therapeutic efficacy in patients who had OAB with CNS disorders, especially in cerebrovascular accident and parkinsonism. No OAB medication or their combination affected cognitive function, whereas minimal AEs were noted with mirabegron. Mirabegron could be recommended as the first choice for managing OAB in these patients.